2014
DOI: 10.1177/2325967114532762
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Pull-out Strength for Different Bone Block Length in a Porcine Anterior Cruciate Ligament Model

Abstract: Background:Bone block length for bone–patellar tendon–bone (BPTB) anterior cruciate ligament (ACL) reconstruction has traditionally been 25 mm in length. The previous surgical technique did not require the surgeon to pay particular attention to the length of the bone block, and therefore, there is scant evidence in the literature describing ideal lengths. With the gaining popularity of accessory medial portal drilling of the femoral tunnel, concerns with tunnel length and graft shuttling have surfaced. Newer t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 14 publications
1
6
0
1
Order By: Relevance
“…Porcine knees are used as a comparative model for femur fixation, 13 and previous studies reported their similar biomechanical properties. [14][15][16][17] The knees were dissected evenly. After skin and subcutaneous removal, patellar and quadriceps tenotomy, in addition to all extensor tendons, was performed, except in group 3, and the graft was fixed through an adductor tenodesis.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Porcine knees are used as a comparative model for femur fixation, 13 and previous studies reported their similar biomechanical properties. [14][15][16][17] The knees were dissected evenly. After skin and subcutaneous removal, patellar and quadriceps tenotomy, in addition to all extensor tendons, was performed, except in group 3, and the graft was fixed through an adductor tenodesis.…”
Section: Methodsmentioning
confidence: 99%
“…Porcine knees are used as a comparative model for femur fixation, 13 and previous studies reported their similar biomechanical properties. 14 15 16 17 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…20,21 Bone plug length has been shown to effect fixation stability in femoral and tibial porcine models, with < 10 mm plug lengths led to significantly reduced failure loads compared with plug lengths of 10-and 15-mm. 22,23 The potential benefits of harvesting shorter plugs, likely more significant on the patellar side, include minimizing the stress riser and potential donor site morbidity, especially in smaller-statured patients. 24 Additionally, as many surgeons have gone to independent drilling of the femoral tunnel (anteromedial portal method 20,23 ), the femoral bone plug from the BPTB graft needs to be delivered around a more acute angle into the femoral tunnel.…”
mentioning
confidence: 99%
“…22,23 The potential benefits of harvesting shorter plugs, likely more significant on the patellar side, include minimizing the stress riser and potential donor site morbidity, especially in smaller-statured patients. 24 Additionally, as many surgeons have gone to independent drilling of the femoral tunnel (anteromedial portal method 20,23 ), the femoral bone plug from the BPTB graft needs to be delivered around a more acute angle into the femoral tunnel. Longer bone plugs may make this technically more difficult.…”
mentioning
confidence: 99%